Concurrent Validity of Power From Three On-Water Rowing Instrumentation Systems and a Concept2 Ergometer - Holt, Ana C.; Hopkins, William G.; Aughey, Robert J.; Siegel, Rodney; Rouillard, Vincent; Ball, Kevin (Frontiers in Physiology, 2021)
Purpose: Instrumentation systems are increasingly used in rowing to measure training intensity and performance but have not been validated for measures of power. In this study, the concurrent validity of six Peach PowerLine, five Neilsen-Kellerman EmPower, three Weba OarPowerMeter units, one Concept2 model D ergometer, and a custom-built reference instrumentation system (Reference System) were investigated. Methods: Eight female and seven male rowers (age, 21 ± 2.5 y; rowing experience, 7.1 ± 2.6 y; mean ± SD) performed a 30-s maximal test and a 7x4-min incremental test once per week for 5 wk. Power per stroke was extracted concurrently from the Reference System (via chain force and velocity), the Concept2 itself, Weba (oarshaft-based), and either Peach or EmPower (oarlock-based). Differences from the Reference System in the mean (representing potential error) and the stroke-to-stroke variability (SD) of power per stroke for each stage and device, and between-unit differences, were estimated using general linear mixed modelling and interpreted using rejection of non-substantial and substantial hypotheses. Results: Potential error in mean power was decisively substantial for all devices (Concept2, -11 to -15%; Peach, -7.9 to -17%; EmPower, -32 to -48%; Weba, -7.9 to -16%). Between-unit differences (as SD) in mean power lacked statistical precision but were substantial and consistent across stages (Peach, ~5%; EmPower, ~7%; Weba, ~2%). Most differences from the Reference System in stroke-to-stroke variability of power were possibly or likely trivial or small for Peach (-3.0 to -16%), and likely or decisively substantial for EmPower (9.7 to 57%), and mostly decisively substantial for Weba (61 to 139%) and the Concept2 (-28 to 177%). Conclusion: Potential negative error in mean power was evident for all devices and units, particularly EmPower. Stroke-to-stroke variation in power showed a lack of measurement sensitivity (apparent smoothing) that was minor for Peach but larger for the Concept2, whereas EmPower and Weba added substantial random error. Peach is therefore recommended for measurement of mean and stroke power.